Parental Knowledge about Caries Prevention in Children Aged 2-6 Years Old in Batam - Tsamara N. Randhika; Andi Supriatna; Mutiara S. Suntana (e-GiGi, 2022)
Abstract: The incidence of caries in children is still very high in Indonesia. Parental knowledge can be assessed, among others, from the level of parental knowledge regarding caries prevention in children. The higher the level of parental knowledge, the better the parenting pattern, especially in educating children to maintain their healthy teeth and mouths. This study aimed to describe the parental level of knowledge regarding caries prevention in children aged 2-6 years in Batam, Indonesia based on education and occupation levels. This was a descriptive and observational study with a cross-sectional design. This study was conducted by distributing questionnaires using google-form to eight kindergartens and social media. The results obtained 145 parents as respondents; 43 respondents had poor knowledge, 88 had moderate knowledge, and 14 had good knowledge. From the respondents with moderate knowledge, 80.7% had college education and 36.4% worked as private employees. In conclusion, the majority of parents with moderate level of knowledge about caries prevention in children aged 2-6 years in Batam were college educated and worked as private employees. Keywords: caries; level of knowledge; occupation; parental knowledge Abstrak: Angka kejadian karies pada anak masih sangat tinggi di Indonesia. Tingkat pengetahuan orang tua dapat dinilai antara lain dari tinggi rendahnya pengetahuan orang tua mengenai pencegahan karies pada anak. Semakin tinggi tingkat pengetahuan orang tua akan semakin baik pula pola asuh orang tua terutama dalam mendidik anak untuk menjaga kesehatan gigi dan mulutnya. Penelitian ini bertujuan untuk mengetahui gambaran tingkat pengetahuan orang tua mengenai pencegahan karies pada anak usia 2-6 tahun di Kota Batam, Indonesia, berdasarkan tingkat pendi-dikan dan pekerjaan. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang yang bersifat data tetap, Penelitian dilakukan dengan menyebarkan kuisioner menggunakan google-form ke delapan Taman Kanak-kanak (TK) dan media sosial. Hasil penelitian mendapatkan jumlah responden sebanyak 145 orang tua. Tingkat pengetahuan kurang pada 43 responden; cukup, pada 88 responden; dan baik, pada 14 responden. Pada tingkat pengetahuan cukup, 80,7% responden berpendidikan perguruan tinggi dan 36,4% responden sebagai pegawai swasta. Simpulan penelitian ini ialah mayoritas orang tua dengan tingkat pengetahuan cukup mengenai pencegahan karies anak usia 2-6 tahun di Kota Batam mempunyai pendidikan perguruan tinggi dan bekerja sebagai pegawai swasta. Kata kunci: karies; orang tua; pekerjaan; tingkat pengetahuan orang tua